Higher School Marketing Strategy Formation: Classifying the Factors - N. K. Shemetova (Russian State Vocational Pedagogical University, 2015)
The paper deals with the main trends of higher school management strategy formation. The author specifies the educational changes in the modern information society determining the strategy options. For each professional training level the author denotes the set of strategic factors affecting the educational service consumers and, therefore, the effectiveness of the higher school marketing. The given factors are classified from the stand-points of the providers and consumers of educational service (enrollees, students, graduates and postgraduates). The research methods include the statistic analysis and general methods of scientific analysis, synthesis, induction, deduction, comparison, and classification. The author is convinced that the university management should develop the necessary prerequisites for raising the graduates' competitiveness in the labor market, and stimulate the active marketing policies of the relating subdivisions and departments. In author's opinion, the above classification of marketing strategy factors can be used as the system of values for educational service providers.